3'-Formyl phosphate-ended DNA: high-energy intermediate in antibiotic-induced DNA sugar damage. - Chin, D H (1987)
Under anaerobic conditions where the nitroaromatic radiation-sensitizer misonidazole substitutes for dioxygen, DNA strand breakage (gaps with phosphate residues at each end) by the nonprotein chromophore of the antitumor antibiotic neocarzinostatin (NCS-Chrom) is associated with the generation of a reactive form of formate from the C-5' of deoxyribose of thymidylate residues. Such lesions account for a minority (10-15%) of the strand breakage found in the aerobic reaction without misonidazole. Amino-containing nucleophiles such as tris(hydroxymethyl)aminomethane (Tris) and hydroxylamine act as acceptors for the activated formate. The amount of [3H]formyl hydroxamate produced from DNA labeled with [5'-3H]thymidine is comparable to the spontaneously released thymine. During the course of the reaction, misonidazole undergoes a DNA-dependent reduction and subsequent conjugation with glutathione used to activate NCS-Chrom. From these and earlier results, we propose a possible mechanism in which the carbon-centered radical formed at C-5' by hydrogen atom abstraction by thiol-activated NCS-Chrom reacts anaerobically with misonidazole to form a nitroxyl-radical-adduct intermediate, which fragments to produce an oxy radical at C-5'. beta-Fragmentation results in cleavage between C-5' and C-4' with the generation of 3'-formyl phosphate-ended DNA, a high-energy form of formate, which spontaneously hydrolyzes, releasing formate and creating a 3'-phosphate end, or transfers the formyl moiety to available nucleophiles. A similar mechanism, involving dioxygen addition, is probably responsible for the 10-15% DNA gap formation in the aerobic reaction.